Bahasa Inggris - Deva Ratu Wyasa; Ervina CM Simatupang (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2025)
This study looks at the pragmatics functions of swearing in Matt Rife's stand-up comedy special Lucid : A Crowd Work Special. The study takes a qualitative descriptive method, analyzing transcribed interactions to categorize swearing types and explain their meanings using Andersson and Trudgill’s (1990) framework. The analysis identifies five strategies uses of swearing: (1) annoyance (as emotional intensification), (2) social (building audience solidarity through identity-based humour), (3) abusive (playful insult like “bullshit” for exaggerated effect), (4) humorous (taboo-breaking phrases such as “fuck yeah” to shock value) and (5) expletive (spontaneous outburst like “Get the fuck out”). The findings show that five distinct types of swearing employed throughout the performance. Humorous swearing emerged as the most prevalent type, accounting for 36% of the total data, abusive swearing followed closely with 32%, social swearing appeared 20%, expletive swearing was found in 8%, and finally, annoyance swearing appeared least frequently with only 4%. This distribution demonstrates that Rife strategically employs diverse types of swearing to maximize comedic impact while maintaining audience engagement throughout the unscripted crowd-work performance. Limitations include the focus on a single comedian’s work, implying that future research may evaluate swearing functions across comedic genres or cultures. Finally, the study emphasizes that context plays a crucial role in interpreting swearing, where in comedy, its function shifts into a tool for social bonding and entertainment